Computational Method for Sizing and Cost Analysis of Grid-Connected Photovoltaic System - Ahmad, Nurul Izzati; Nor, Ahmad Fateh Mohamad (Journal of Quranic Sciences and Research, 2022)
This study is focuses on the computational method used for a sizing and cost analysis of grid-connected photovoltaic system. These calculations include total load consumption, photovoltaic sizing, total energy production, tariff calculation, costing and return on investment. This calculation is important to ensure that the equipment used does not produce excessive energy which is related to cost and Return On Investment (ROI). This study will cover the computational method in house at Taman Impian, Partit Raja, Batu Pahat, Johor.